Effect of recycle tire isolator as earthquake resistance system for low rise buildings in Malaysia - Sow, Wei Jie*; Siow, Yun Tong*; Anuar, Kasa; Osman, S. A. (School of Engineering,Taylor’s University, 2016)
The purpose of this research is to investigate the effect of Recycle Tire Isolator (RTI) as earthquake resistance system for low rise buildings in Malaysia. Most of the earthquake’s victims are due to the collapse of poorly designed concrete and masonry buildings. Therefore, an economical but reliable RTI is introduced to solve the problem in most of the developing countries such as Malaysia. This study focuses on the effect of RTI-5 (5 layers RTI) in protecting three stories buildings. The vertical displacement of RTI-5 was determined through static compression test. The maximum vertical displacement of RTI-5 was obtained when the specimen was monotonically loaded to failure. Finite element analysis was carried out by using ANSYS V16.0 to model the RTI-5 and the results obtained were compared to the experimental results. The dynamic stiffness and damping ratio of RTI-5 were investigated through dynamic test. The behaviour of various thickness of RTI were examined and compared with Rubber Bearing (RB) and Scrap Tire Rubber Pad (STRP).Total displacement of three stories buildings on fixed base and on base isolation were determined. The results from static compression test and finite element analysis showed that RTI-5 could sustain a vertical load of 380 kN with vertical deformation of 12.5 mm. It has been verified by finite element analysis (FEA) where both of the results achieved close agreement in terms of vertical deformation. RTI-5 and STRP have similar vertical stiffness due to the employment of same material in fabrication. However, rubber bearing is stiffer than RTI-5 due to the present of embedded steel plates. Besides, RTI-4 is stiffer than RTI-5 due to the number of layers are lesser in RTI-4. The results of dynamic test shown that RTI-5 has higher damping ratio than RTI-4. In overall, total deformation at the top floor of the three stories building is reduced by 83% via implementation of RTI in the base of the building. It has been proven that RTI can reduce the total displacement of low rise building effectively